Interplay between H1 and HMGN epigenetically regulates OLIG1&2 expression and oligodendrocyte differentiation. Issue 6 (6th December 2016) - Deng, Tao; Postnikov, Yuri; Zhang, Shaofei; Garrett, Lillian; Becker, Lore; Rácz, Ildikó; Hölter, Sabine M.; Wurst, Wolfgang; Fuchs, Helmut; Gailus-Durner, Valerie; de Angelis, Martin Hrabe; Bustin, Michael
Abstract: An interplay between the nucleosome binding proteins H1 and HMGN is known to affect chromatin dynamics, but the biological significance of this interplay is still not clear. We find that during embryonic stem cell differentiation loss of HMGNs leads to down regulation of genes involved in neural differentiation, and that the transcription factor OLIG2 is a central node in the affected pathway. Loss of HMGNs affects the expression of OLIG2 as well as that of OLIG1, two transcription factors that are crucial for oligodendrocyte lineage specification and nerve myelination. Loss of HMGNs increases the chromatin binding of histone H1, thereby recruiting the histone methyltransferase EZH2 and elevating H3K27me3 levels, thus conferring a repressive epigenetic signature at Olig1&2 sites. Embryonic stem cells lacking HMGNs show reduced ability to differentiate towards the oligodendrocyte lineage, and mice lacking HMGNs show reduced oligodendrocyte count and decreased spinal cord myelination, and display related neurological phenotypes. Thus, the presence of HMGN proteins is required for proper expression of neural differentiation genes during embryonic stem cell differentiation. Specifically, we demonstrate that the dynamic interplay between HMGNs and H1 in chromatin epigenetically regulates the expression of OLIG1&2, thereby affecting oligodendrocyte development and myelination, and mouse behavior.